Chiral Phosphoric Acids in Metal–Organic Frameworks with Enhanced Acidity and Tunable Catalytic Selectivity. Issue 41 (5th September 2019) - Chen, Xu; Jiang, Hong; Li, Xu; Hou, Bang; Gong, Wei; Wu, Xiaowei; Han, Xing; Zheng, Fanfan; Liu, Yan; Jiang, Jianwen; Cui, Yong
Abstract: Chiral phosphoric acids are incorporated into indium‐based metal–organic frameworks (In‐MOFs) by sterically preventing them from coordination. This concept leads to the synthesis of three chiral porous 3D In‐MOFs with different network topologies constructed from three enantiopure 1, 1′‐biphenol‐phosphoric acid derived tetracarboxylate linkers. More importantly, all the uncoordinated phosphoric acid groups are periodically aligned within the channels and display significantly enhanced acidity compared to the non‐immobilized acids. This facilitates the Brønsted acid catalysis of asymmetric condensation/amine addition and imine reduction. The enantioselectivities can be tuned (up to >99 % ee ) by varying the substituents to achieve a nearly linear correlation with the concentrations of steric bulky groups in the MOFs. DFT calculations suggest that the framework provides a chiral confined microenvironment that dictates both selectivity and reactivity of chiral MOFs. Abstract : Chiral phosphoric acids can be constructed into metal–organic frameworks (MOFs) by sterically preventing them from coordination. This leads to three chiral porous 3D In‐MOFs with different network topology from three tetracarboxylate linkers derived from enantiopure 1, 1′‐biphenol‐phosphoric acid.